Effects of moderate drought extension on bacterial network structure in the rhizosphere soil of Leymus chinensis in semi-arid grasslands - Wang, Jinlong; Wang, Chunjuan; Wu, Xuefeng; Zhang, Jinwei; Zhao, Guiyun; Hou, Yu; Sun, Haiming (Frontiers in Microbiology, 2023)
Grasslands are home to complex bacterial communities whose dynamic interactions play a crucial role in organic matter and nutrient cycling. However, there is limited understanding regarding the impact of changes in rainfall amount and the duration of dry intervals on bacterial interactions. To assess the impact of changes in precipitation volume and dry intervals on bacterial co-occurrence networks, we carried out precipitation manipulation experiments in the Eastern Eurasian Steppe of China. We found that alterations in precipitation and dry intervals did not significantly affect bacterial alpha and beta diversity. However, we observed significant changes in the co-occurrence network structure of bacteria in the rhizosphere ecosystem, with the 12-day dry interval showing the most notable reduction in the number of degrees, edges, and clustering coefficient. Additionally, the study identified putative keystone taxa and observed that the moderately prolonged dry intervals between precipitation events had a major effect on the robustness of bacterial networks. The complexity and stability of the network were found to be positively correlated, and were primarily influenced by soil water content, phosphorous, and aboveground biomass, followed by available phosphorus (AP) and total biomass. These findings have the potential to enhance our comprehension of how bacterial co-occurrence pattern react to variations in dry intervals, by regulating their interactions in water-limited ecosystems. This, in turn, could aid in predicting the impact of precipitation regime alterations on ecosystem nutrient cycling, as well as the feedback between ecosystem processes and global climate change.